Study for analyzing world judo player's technical type and time - Kim, T.-W.; Lee, S.-H. (Korean Journal of Sport Science, 2020)
Purpose: Based on the match data of major judo world competitions in the last five years, this study identifies differences in general characteristics and environmental factors according to scoring technique and scoring times. And by exploring the factors associated with scoring technique, I would like to present a practical strategy that can be used to establish guided tactics.